2008
DOI: 10.1080/01421590801949966
|View full text |Cite
|
Sign up to set email alerts
|

Formative feedback to students: the mismatch between faculty perceptions and student expectations

Abstract: There is a need to create awareness among teachers on the usefulness of this tool in higher education and for moulding teaching practices by including training on this aspect of teaching-learning, in routine faculty development activities. The study showed the importance of including feedback as a generic feature in all learning activities, and this may require incorporating into institutional policy for successful implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 17 publications
4
68
0
5
Order By: Relevance
“…Indeed, 72.4% were in agreement that generic examination feedback would help improve their performance, whereas 91% strongly agreed or agreed that individual feedback was more beneficial to their learning than generic (class) feedback. This mirrors research by Perera 28 who found that students wanted more individualized feedback. While the level of detail also was deemed by students to be an important consideration, it can be a 2-edged sword.…”
Section: Discussionsupporting
confidence: 61%
“…Indeed, 72.4% were in agreement that generic examination feedback would help improve their performance, whereas 91% strongly agreed or agreed that individual feedback was more beneficial to their learning than generic (class) feedback. This mirrors research by Perera 28 who found that students wanted more individualized feedback. While the level of detail also was deemed by students to be an important consideration, it can be a 2-edged sword.…”
Section: Discussionsupporting
confidence: 61%
“…In spite of claims about the power of feedback to produce positive learning effects (Black & Wiliam, 1998;Hattie & Timperley, 2007), within the HE context, there are concerns regarding the perceived lack of impact of feedback on practice (Perera, Lee, Win, Perera, & Wijesuriya, 2008). Evidence of progress in improving feedback practices is seen to be lacking (Orrell, 2006), conflicting, and inconsistent (Shute, 2008).…”
Section: The Higher Education Contextmentioning
confidence: 99%
“…having to carry much of the burden of teacher-student interaction" (p. 503). Written feedback does not have to be a monologue and a one-way process (Black & McCormick, 2010;Perera et al, 2008). Orsmond et al (2005) argued that feedback should be seen as the focal point for group work and that lecturers need to evaluate how their feedback to students is utilized.…”
Section: Power: the Respective Roles Of Student And Lecturer Within Tmentioning
confidence: 99%
“…Otros procedimientos, como la misma explora ción física u otros procedimientos manuales, se pueden supervisar invitando al estudiante a que los repita una vez ha visto como los realizamos (con las limitaciones obvias de cada caso), y viceversa, tras realizarla el estudiante, nosotros la repetiremos y en su caso corregiremos. La tutorización directa de las habilidades clínicas tendrá efectos duraderos en los hábitos del estudiante a condición de seguir al guna sencillas recomendaciones [10] (que sin em bargo no suelen realizarse [11] ¿Ha sido suficientemente minucioso en la recogida de datos?…”
Section: Dar Feedback Al Estudianteunclassified